(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of HIV (Human immunodeficiency virus) infection and co-infection with HBV (Hepatitis B virus) and/or HCV (Hepatitis C virus) in HIV-positive patients examined and treated at Military Hospital 103 from January 2017 to December 2023. Subjects and Methods: A cross-sectional descriptive study was conducted on patients who were tested for HIV during the period from January 2017 to December 2023. Results: The average HIV infection rate among patients tested at Military Hospital 103 was 0.21%. HIV infection was most common in 30 - 39 age group, accounting for 35.38%, and least common in individuals aged ≤ 19 (3.59%). The male-to-female ratio was 2.8:1. Among HIV-infected individuals, the prevalence of co-infection with HBV and/or HCV is 38.21%. Specifically, 25.13% are co-infected with HCV, 11.03% with HBV, and 2.05% are co-infected with both HBV and HCV. Conclusion: This study conducted at Military Hospital 103 from January 2017 to December 2023 showed an HIV detection rate among tested patients was 0.21%. The proportion of HIV infection was high in the 30 - 39 years and male individuals. The rate of HIV patients co-infected with HBV and/or HCV is relatively high (38.21%).